Canadian Attitudes towards Jews and Muslims, 2025 - Brym, Robert (Canadian Jewish Studies / Études juives canadiennes, 2025)
Jews and Muslims are two of the most dissimilar groups in Canada society in terms of their sociodemographic characteristics. Layered on top of those differences is antagonism over the Israel-Palestine conflict. Yet this report, based on a January 2025 web panel survey of 2,821 Canadian adults, shows that Jews and Muslims have some things in common. Notably, a considerable number of Canadians have negative attitudes toward both groups. Negative attitudes toward Jews and Muslims are correlated with more general racist sentiment. And although more Canadians express negative attitudes toward Muslims than Jews, negative attitudes toward both groups are stronger than the Canadian average in Montreal and especially Quebec City. They are weaker than the Canadian average in Vancouver, Calgary, Edmonton, and especially Winnipeg. However, intercity differences fail to reach statistical significance at standard levels once other factors are taken into account. In other words, the reason some cities have populations with more negative attitudes toward Jews and Muslims is that they have a greater percentage of people who have other characteristics associated with these negative attitudes. Specifically, the non-Jewish Canadians most likely to have negative attitudes toward Jews say have had negative experiences with Jews. They tend to be Quebecois and place themselves on the right of the political spectrum. They are likely to lack even a single Jewish acquaintance and to be relatively young. They are unlikely to support the New Democratic Party and they tend to identify as male. Similarly, the non-Muslim Canadians who are most likely to have negative attitudes toward Muslims say have had negative experiences with Muslims and are likely to place themselves on the right of the political spectrum. They, too, tend to be Quebecois. There is a disproportionately large number of Conservative Party supporters among them. Finally, they lack even a single Muslim friend. Compared to the general population of Canada, individuals on the political left tend to have less negative attitudes towards Jews and more negative attitudes toward Israel. Leftists often claim they are not antisemitic, but most Canadian Jews disagree because strongly negative attitudes toward Israel effectively deny Jews a core part of their identity as Jews, namely support for a Jewish state. One of the key findings of this survey is that even Muslim respondents who say they have had good experiences with Jews tend not to have negative attitudes toward Jews, while even Jews who say they have had good experiences with Muslims tend not to have negative attitudes toward Muslims. The report ends by considering the implications of this finding for Jewish-Muslim relations in Canada.